CHRONIC KIDNEY DISEASE PREVENTION DEVELOPMENT MODEL BY SOCIAL SUPPORT, SUB-DISTRICT HEALTH PROMOTING HOSPITALS - Petcharee, Tammarat (Journal of MCU Nakhondhat, 2024)
This article aims to develop a chronic kidney disease prevention model for sub-district health-promoting hospitals, using social support. It is a mixed-methods study with the objectives of studying the current situation of chronic kidney disease prevention, creating a prevention model, testing, and evaluating its effectiveness.The sample in Phase 1 consisted of 490 individuals at risk of chronic kidney disease (calculated using a formula), 16 healthcare personnel, 12 service recipients, and 10 community stakeholders involved in the network, selected using purposive sampling. In Phase 2, 13 registered nurses were selected using purposive sampling. In Phase 3, 70 individuals at risk of chronic kidney disease were selected using G*power. The research instruments included in-depth interview guidelines, focus group discussions, a health behavior questionnaire with a content validity index of 0.87, and a Cronbach’s alpha reliability coefficient of 0.85. The statistical analysis included frequency, percentage, mean, thematic analysis, and t-test statistics. The study found that the chronic kidney disease prevention model in Mueang District, Phitsanulok Province, must involve the participation of healthcare personnel, service recipients, and related community stakeholders. The model should emphasize comprehensive and systematic support, including emotional, informational, instrumental, and evaluative support, which enhances the effectiveness of disease prevention and reduces the risk of chronic kidney disease in the long term. After the third phase of the research, the average health behaviors, sodium levels in food, and blood pressure of the experimental group who received care under the social support-based chronic kidney disease prevention model were significantly different from the control group.